Combined Microscopic and Metabolomic Approach to Characterize the Skeletal Muscle Fiber of the Ts65Dn Mouse, A Model of Down Syndrome. (October 2020) - Cisterna, Barbara; Sobolev, Anatoly P.; Costanzo, Manuela; Malatesta, Manuela; Zancanaro, Carlo
Abstract: Abstract : Down syndrome (DS) is a genetically based disease caused by triplication of chromosome 21. DS is characterized by severe muscle weakness associated with motor deficits; however, understanding the DS-associated skeletal muscle condition is limited. In this study, we used a combined methodological approach involving light and electron microscopy, as well as nuclear magnetic resonance spectroscopy metabolomics, to investigate morphology and composition of the quadriceps muscles in the Ts65Dn mouse, a model of DS, to identify structural and/or functional trisomy-associated alterations. Morphometric analysis demonstrated a larger size of myofibers in trisomic versus euploid mice; however, myofibrils were thinner and contained higher amounts of mitochondria and lipid droplets. In trisomic mice, magnetic resonance spectroscopy showed a tendency to an overall increase in muscle metabolites involved in protein synthesis. These data strongly suggest that in DS, a sarcoplasmic hypertrophy associated with myofibril loss characterizes quadriceps myofibers. In addition, large-sized mitochondria suggestive of impaired fission/fusion events, as well as metabolites modifications suggestive of decreased mitochondrial function, were found in the trisomic muscle. Albeit preliminary, the results provided by this novel approach consistently indicate structural and compositional alterations of the DS skeletal muscle, which are typical of early aging.